(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to analyze the published scientific production regarding nursing care regarding the use of electrosurgery, and to identify their contributions to the quality of care. Methodology: It is na integrative review, using the studies published in the last twenty years in the LILACS and MEDLINE® databases via PubMed, in the VHL- Nursing and Scielo Libraries, and in the Google Scholar portal. The data collection period occurred from 01/08/2020 to 31/10/2020. Results: Twenty-four studies were found that, when analyzing the essence of the contents, it was found that in 62.5% they addressed the knowledge of the nursing team about the use of electrosurgery. In approximately 60% of the articles, they mentioned the need to adopt patient safety measures to minimize the potential risks of the electrosurgery unit, and only 33.3% of the publications addressed the role of the perioperative nurse to favor and guarantee prevention and safety in the use of electrosurgery. In this sense, the need emerges to have a nursing team aligned with the needs of patients andwith the ability to prevent the various injuries that occur, mainly, in the operating rooms. Conclusion: The results of this study indicate a scientific production still in progress, and point out that the nursing team is among the professionals who play na important and indispensable role in the care of electrosurgery in the intraoperative period.